2010
DOI: 10.1111/j.1349-7006.2010.01583.x
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant engineering for cancer immunotherapy: Development of a synthetic TLR2 ligand with increased cell adhesion

Abstract: The development of effective immunoadjuvants for tumor immunotherapy is of fundamental importance. The use of Mycobacterium bovis bacillus Calmette-Gué rin cell wall skeleton (BCG-CWS) in tumor immunotherapy has been examined in various clinical applications. Because BCG-CWS is a macromolecule that cannot be chemically synthesized, the development of an alternative synthetic molecule is necessary to ensure a constant supply of adjuvant. In the present study, a new adjuvant was designed based on the structure o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 47 publications
0
41
0
Order By: Relevance
“…Synthetic lipopeptides derived from Braun's lipoprotein were shown to exhibit stimulatory activity comparable to that of native lipoproteins (24). It was also shown that a TLR2 agonist, which is the hDC TLR that recognizes M. hominis (8), required a hydrophilic N-terminal part (25). The DSL-1 peptide chosen had seven N-terminal amino acid residues (CGGEKFN), which conferred a negative grand average of hydropathy (GRAVY) score close to that of the bioactive mycoplasmal lipopeptides FSL-1 and MALP-2 (11, 12) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic lipopeptides derived from Braun's lipoprotein were shown to exhibit stimulatory activity comparable to that of native lipoproteins (24). It was also shown that a TLR2 agonist, which is the hDC TLR that recognizes M. hominis (8), required a hydrophilic N-terminal part (25). The DSL-1 peptide chosen had seven N-terminal amino acid residues (CGGEKFN), which conferred a negative grand average of hydropathy (GRAVY) score close to that of the bioactive mycoplasmal lipopeptides FSL-1 and MALP-2 (11, 12) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…future science group adjuvants and novel therapeutic agents targeting cancer [32][33][34] and allergy [35].…”
Section: Self-adjuvanting Vaccinesmentioning
confidence: 99%
“…2A). In this context, three markers for NK activation (19) were assessed with this system, IFN-γ production, up-regulation of NK activation markers and target cell (B16D8) cytotoxicity by NK cells (Fig. 2).…”
Section: Nk Activation By Pam2csk4 and Malp-2mentioning
confidence: 99%